Pengaruh Penggunaan Smart Box terhadap Hasil Belajar IPAS Siswa Kelas V SDN Gugus III Kota Bengkulu: Smart Box Learning Media - Utami, Heni Tri; Kurniawati, Ike (Universitas Bengkulu, 2025)
This study aims to determine the effect of the use of smart box learning media on the learning outcomes of Natural and Social Sciences (IPAS) of fifth-grade students at SDN Gugus III, Bengkulu City. The method used in this study is quantitative with a quasi-experimental approach and the Matching Only Pretest-Posttest Control Group Design. The population in this study were fifth-grade students of cluster III, Bengkulu City. While the research sample consisted of two groups, namely class VA students of SDN 17, Bengkulu City as the experimental group and class V students of SDN 57, Bengkulu City as the control group. Data collection techniques were carried out through pretest and posttest tests in the form of multiple-choice questions to measure student learning outcomes that had been prepared according to learning objectives and cognitive level indicators. The results of the hypothesis test in the experimental group showed that the t count value > t table (3.217 > 2.021) and Sig. (2-tailed) 0.003 < 0.05. These data indicate that there are differences in learning outcomes in the experimental group and the control group due to different treatments, namely learning using smart box media in the experimental group and conventional learning without using smart box media in the control group. Based on these results, it can be concluded that there is an influence of the use of smart box learning media on the science learning outcomes of fifth-grade students at SDN Cluster III, Bengkulu City.